Towards iVProg4All: An Accessibility Test with Blind - Do Nascimento, Marcos D.; Brandao, Anarosa A. F.; De Oliveira Brandao, Leonidas; Casal, Tiago Melo (Proceedings - Frontiers in Education Conference, 2023)
Computational thinking has become an essential skill nowadays. Many educational institutions around the world have adopted computational thinking as an elementary or complementary subject in their teaching schedules. One of the approaches that is efficient in teaching and learning computational thinking has been visual programming. However, like other applications used daily, visual programming tools can be a limiting factor for the blind in learning computational thinking. This work aims to present the iVProg4all, an accessible visual programming system based on forms. A preliminary study was carried out to test the usability of iVProg4all and accessibility with a blind user. The results show that, although some usability issues need to be fixed, the system proved accessible for blind people.